Actions of Academic Institutions for Optimization of Human Capital - Mishra, Anjay (Apex Journal of Business and Management, 2024)
This editorial integrates the pivotal role of human capital, intellectual capital, and innovation in the pursuit of national prosperity and organizational success. As organizations endeavor to optimize human capital, recognizing it as a cornerstone of value creation, we emphasize the need for strategic investments in education, training, and innovative workforce development. By doing so, nations can position themselves at the forefront of global competitiveness, fostering inclusive growth and prosperity. Through the exploration of complexities in human and intellectual capital, we encourage researchers, practitioners, and policymakers to adopt innovative approaches. The contributions in this issue aim to broaden our understanding of the interconnected dynamics between human capital, intellectual assets, and organizational success.